Platelet to lymphocyte ratio is associated with tumor localization and outcomes in metastatic colorectal cancer. Issue 44 (5th November 2021) - Acikgoz, Ozgur; Cakan, Burcin; Demir, Tarik; Bilici, Ahmet; Oven, Bala Basak; Hamdard, Jamshid; Olmuscelik, Oktay; Olmez, Omer Fatih; Seker, Mesut; Yildiz, Ozcan
Abstract : Abstract: The aim of this study was to investigate the predictive and prognostic value of PLR, and the relationship between PLR and tumor localization. A total of 229 patients with de-novo metastatic CRC were retrospectively analyzed. The cutoff value for PLR was defined by the receiver operating characteristic (ROC) curve analysis and threshold value of 196.5 as best cut-off value was found. The higher rate of BRAF mutation was significantly detected for patients with PLR high (> 196.5) compared to those with PLR low (≤196.5) ( P = .001). PLR was significantly higher in tumors located on the right colon ( P = .012). PLR, tumor localization, the presence of surgery for primary tumor, the presence of curative surgery, the presence of metastasectomy for progression-free survival (PFS) and PLR, gender, BRAF mutation, tumor localization, the presence of surgery for primary tumor, the presence of metastasectomy for overall survival (OS) were found to be prognostic factors by univariate analysis. Multivariate analysis showed that PLR, the presence of curative surgery and the presence of metastasectomy for both PFS and OS were found to be independent prognostic factors. Moreover, a logistic regression analysis indicated that PLR and tumor localization were found to be an independent factors for predicting response to systemic treatment ( P < .001 and P = .023 respectively). Our results showed that pretreatment PLR was readily feasible and simple biomarker predicting response to treatment and survival, in addition it was significantly associated with tumor localization.